# Subract by adding the opposite. A) -14-(-3) B). 0-(-5) C).-17-(-20) D).-0.6-0.3 E)-3/4-5/6)

*print*Print*list*Cite

Note that when a negative number is preceded by another negative, the resulting sign of the number is positive.

Example: `- (-18)=18`

It is like multiplying numbers with like signs. Re-writing the example as multiplication of numbers with like signs gives the same result.

Example: `-(-18)=-1(-18)=18`

Also, when adding two numbers with unlike signs, to determine the result, disregard the signs of the numbers first. Then, subtract. And the resulting value copy the sign of the larger number.

Applying these to the given problem yields:

(A)` -14-(-13)=-14+13=-1`

(B) `0 - (-5)=0+5=5`

(C) `-17-(-20)=-17+20=3`

Moreover, when subtracting numbers with unlike signs, change the sign of the subtrahend to its opposite. Also, change the operation from subtraction to addition. From here, follow the rules of addition for like and unlike signs.

(D) -0.6-0.3= -0.6+(-0.3)=-0.9

(E) `-3/4-5/6=-3/4+(-5/6)=-3/4*3/3 +(-5/6*2/2) = -9/12+(-10/12) =-19/12`

--------------------------------------------------------------------------------

**Answers: (A) -1, (B) 5, (C) 3, (D) -0.9 and (E) -19/12**